2012
DOI: 10.1029/2012ja017825
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seasonal and diurnal variations in the Earth's magnetic dipole orientation on solar wind–magnetosphere‐ionosphere coupling

Abstract: .[1] The angle m between the geomagnetic dipole axis and the geocentric solar magnetospheric (GSM) z axis, sometimes called the "dipole tilt," varies as a function of UT and season. Observations have shown that the cross-polar cap potential tends to maximize near the equinoxes, when on average m = 0, with smaller values observed near the solstices. This is similar to the well-known semiannual variation in geomagnetic activity. We use numerical model simulations to investigate the role of two possible mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…A larger offset between the geographic and invariant magnetic poles (i.e., larger tilt angle) is also expected to lead to greater variation over the course of a day. Cnossen et al [] showed that the cross‐polar cap potential minimizes when the polar cap is tilted maximally towards or away from the Sun (during equinox at 04:40 UT and 16:40 UT for a dipole position at 70°W) and maximizes in between (at 10:40 UT and 22:40 UT for the same conditions). The semidiurnal minima are deeper for a larger dipole tilt, with maxima being roughly the same for different dipole tilts [ Cnossen and Richmond , ].…”
Section: Discussionmentioning
confidence: 99%
“…A larger offset between the geographic and invariant magnetic poles (i.e., larger tilt angle) is also expected to lead to greater variation over the course of a day. Cnossen et al [] showed that the cross‐polar cap potential minimizes when the polar cap is tilted maximally towards or away from the Sun (during equinox at 04:40 UT and 16:40 UT for a dipole position at 70°W) and maximizes in between (at 10:40 UT and 22:40 UT for the same conditions). The semidiurnal minima are deeper for a larger dipole tilt, with maxima being roughly the same for different dipole tilts [ Cnossen and Richmond , ].…”
Section: Discussionmentioning
confidence: 99%
“…Cnossen et al . [] concluded that the main impact of “season” on solar wind–magnetosphere coupling was the dipole tilt (70–90%), whereas illumination contributed only 10–30%. Although this would seem to be in disagreement with the conclusions of Lyatsky et al .…”
Section: Discussionmentioning
confidence: 99%
“…The modeling result by Cnossen et al [] indicated that the total potential drop along the dayside reconnection line, which maps down to the polar caps via magnetic field lines, near solstices (large dipole tilt) is lower (weaker solar wind‐magnetosphere coupling) than that near equinoxes using the same solar wind and purely southward directed IMF condition. Since flows in the magnetosheath diverge from the nose, reconnection at such a shifted reconnection line may be affected by the flow that would have a perpendicular component to the reconnection line.…”
Section: Introductionmentioning
confidence: 99%